TINJAUAN YURIDIS TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH ANAK DI INDONESIA - Budi Handayani; Samuji Samuji (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2022)
The growth and development of a nation in the future is largely determined by the quality of children as their younger generation. Therefore the state deserves to provide special coaching and protection to guarantee its physical, mental and social growth and development. To carry out the guidance and provision of protection, support is needed both regarding institutions and legal tools that are more stable and adequate. Children who commit criminal acts should be treated humanely in the best interests of the child, meaning that children who face the law should be sentenced to imprisonment as a last resort. Indonesia already has rules to protect, prosper and fulfill the rights of children, including Law Number 4 of 1979 concerning Child Welfare, Law Number 11 of 2012 concerning Children's Courts and Law Number 35 of 2014 concerning Child Protection. But it does not seem to be enough to bring about a significant change in the fate of children in conflict with the law, and what is expected in reality often cannot be carried out properly because the judge's ruling is more punitive in nature to the detriment of the child himself. Therefore, the system of punishment of children facing the law should pay attention to the interests of children and in accordance with the standards of values and treatment of a number of national and international instruments that apply to children. All these instruments of international law and national legal instruments are intended to provide guarantees of the protection of the rights of the child. Diversion and the concept of Restorative justice need to be considered in handling children's cases. This concept involves all parties in order to improve the child's morale so that the child no longer repeats his actions but the child does not feel like a patient so that it affects the child's mental development. An educational sentencing system should be a priority for judges in passing judgments. Putting a child in prison is always a last resort and with the shortest possible time frame. Placing children in institutions that have better social benefits and functions and improvements for the child, but it is hoped that these institutions can provide special care, protection, education and skills of an educational nature so that they can be useful with the aim of helping them play socially constructive and productive roles in society.